2015
DOI: 10.1016/j.ijheatmasstransfer.2015.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of Al2O3 Nanoparticle Enhanced Ionic Liquids (NEILs) for Concentrated Solar Power (CSP) applications

Abstract: Nanoparticle Enhanced Ionic Liquids (NEILs) were synthesized by dispersing aluminum oxide (Al 2 O 3) nanoparticles in 1-butyl-3-methylimidazolium bis{(trifluoromethyl)sulfonyl}imide, ([C 4 mim][NTf 2 ]) ionic liquids (ILs). The experimental assessment of NEILs includes investigating the effective thermophysical properties and forced convection heat transfer under laminar and turbulent flow regime. The results show that thermal conductivity and heat capacity enhanced up to ~11% and ~49% respectively for 0.9 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 31 publications
3
26
0
1
Order By: Relevance
“…To apply the above methods and construct an accurate model, in the first stage, a set of experimental data points for the network training is introduced. A review of empirical studies has been performed, and the C p values of some NEILs with wide ranges of nanoparticle concentrations and temperatures were found [20,21,[77][78][79]. The total collected experimental dataset (571) was randomly split into two parts: training (75%) and testing (25%) subsets.…”
Section: Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…To apply the above methods and construct an accurate model, in the first stage, a set of experimental data points for the network training is introduced. A review of empirical studies has been performed, and the C p values of some NEILs with wide ranges of nanoparticle concentrations and temperatures were found [20,21,[77][78][79]. The total collected experimental dataset (571) was randomly split into two parts: training (75%) and testing (25%) subsets.…”
Section: Data Preparationmentioning
confidence: 99%
“…Paul et al [20,21] carried out an experimental study and observed an increase in C p of up to 49% compared with the base ILs when Al 2 O 3 nanoparticles were added to pyrrolidinium-and imidazolium-based NEILs. Furthermore, silver nanofluid heat transfer through a tube with twisted tape inserts was tested by Waghole et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…Auch ausgewählte Vertreter aus der noch wachsenden Gruppe ionischer Flüssigkeiten werden aufgrund ihres sehr geringen Dampfdrucks als Wärmeträgermedium bei höheren Temperaturen vorgeschlagen. Durch den Zusatz von Al 2 O 3 ‐Nanopartikeln kann sowohl die Wärmeleitfähigkeit als auch die spezifische Wärmekapazität verbessert werden .…”
Section: Speicherung Von Sensibler Wärmeunclassified
“…The forced convection heat transfer of ILBNFs under laminar and turbulent flow regimes was experimentally studied by Paul [40], with different volume concentrations For future work, due to the wide variety of molten salts and ionic liquids, more systematic experimental investigations are needed. The synthesis method has a great influence on stability and measured values, so it is very worthwhile for further study.…”
Section: Ionic-liquid-based Nanofluidmentioning
confidence: 99%